(untitled) - Sparre, Per (Rome, 1992)
A selection of methods on fish stock assessment is described in detail, with examples of calculations.Special emphasis is placed on methods based on the analysis of length - frequencies.
Đánh giá và quản lý nguồn lợi thủy sản,Đánh giá và quản lý nguồn lợi thủy sản
Keywords: Fishery management,Quản lí nghề cá,Tropical fish,Cá nhiệt đới